2022
DOI: 10.1097/md.0000000000030333
|View full text |Cite
|
Sign up to set email alerts
|

Systemic therapies for metastatic renal cell carcinoma in the second-line setting: A systematic review and network meta-analysis

Abstract: Objectives: To perform a systematic review and network meta-analysis to compare the survival benefit and safety profile of current available second-line treatment options of metastatic renal cell carcinomav. Methods: PubMed, EMBASE, Web of Science, and Cochrane Library were systematically researched for eligible articles which were published before July 20, 2021. Studies comparing overall/progression free survival (OS/PFS), objective response rate (ORR), and/or adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Temsirolimus and everolimus partially inhibit mTORC1 activation, leading to modest survival benefits in advanced RCC patients, according to the results of the phase III Global ARCC trial. 33,34 As reported from a phase II study, everolimus demonstrated mild antitumor effects in metastatic urinary bladder cancer (UBC) patients resistant to chemotherapy. 35 In another phase II study, only a small portion of patients with advanced UBC responded to everolimus.…”
Section: 32mentioning
confidence: 97%
“…Temsirolimus and everolimus partially inhibit mTORC1 activation, leading to modest survival benefits in advanced RCC patients, according to the results of the phase III Global ARCC trial. 33,34 As reported from a phase II study, everolimus demonstrated mild antitumor effects in metastatic urinary bladder cancer (UBC) patients resistant to chemotherapy. 35 In another phase II study, only a small portion of patients with advanced UBC responded to everolimus.…”
Section: 32mentioning
confidence: 97%
“…The main ICI drugs include ipilimumab and tremelimumab for CTLA-4 inhibition; nivolumab, pembrolizumab, and cemiplimab for PD-1 inhibition; and atezolizumab, avelumab, and durvalumab for PD-L1 inhibition [1]. Recent meta-analyses 2 of 11 have shown that ICI treatments, especially a combination of these drugs, can have a significant effect on response rate, free survival, and overall survival for various advanced cancer types (e.g., melanoma, non-small-cell carcinoma, renal cell carcinoma) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Today’s modern imaging led to tumor size and stage migration, the era of incidentaloma, the acceptance of kidney-sparing operations, and, in parallel, the development of minimally invasive surgery (MIS) and ablative techniques [2] . For patients with stage 4 disease, current systemic therapies, including tyrosine kinase, mTOR, immune checkpoint, and HIF2α inhibitors, have led to a fourfold improvement in overall survival (OS) in comparison to historical controls [3] . However, 30–40% of patients with localized disease eventually experience recurrence and surgeons are asked to play a critical role in their care.…”
mentioning
confidence: 99%